Computer vision, imaging and computer graphics. theory and applications : International Joint Conference, VISIGRAPP 2011, Vilamoura, Portugal, March 5-7, 2011. Revised Selected Papers - Kraus, Martin; Mestetskiy, Leonid; Richard, Paul; Braz, José; Csurka, Gabriela (Communications in Computer and Information Science, 2013)
This book constitutes the refereed proceedings of the International Conference, VISIGRAPP 2011, the Joint Conference on Computer Vision, Theory and Applications (VISAPP), on Imaging Theory and Applications (IMAGAPP), on Computer Graphics Theory and Applications (GRAPP), and on Information Visualization Theory and Applications (IVAPP), held in Vilamoura, Portugal, in March 2011. The 15 revised full papers presented together with one invited paper were carefully reviewed and selected. The papers are organized in topical sections on computer graphics theory and applications; imaging theory and applications; information visualization theory and applications; and computer vision theory and applications.